Biopreservative Efficacy of Bacteriocin GP1 of Lactobacillus rhamnosus GP1 on Stored Fish Filets - Sarika, A. R.; Lipton, Aaron P.; Aishwarya, M. S. (Frontiers in Nutrition, 2019)
The bacteriocin based strategy of biopreservation has got wide spread research interests in the recent past for their prospects in reducing usage of chemical preservatives. The bacteriocin GP1 with antibacterial activity and produced by Lactobacillus rhamnosus GP1 was tested for its effect on sensory (colour, odour and appearance), chemical (pH, Total Volatile Base – Nitrogen (TVB-N), Total Methyl Amine (TMA), Total Free Fatty Acid) and bacteriological (total bacterial count, count of Staphylococcus sp., Aeromonas sp., total coliform, Lactobacillus sp., Pseudomonas sp. and Vibrio sp.) quality attributes of fish fillets stored at 4 and 0°C. The sensory attributes of the fish fillets treated with the bacteriocin and control from 7 to 28 days of storage in both the storage temperatures varied significantly. The pH of the raw fish increased from the initial 6.8 to 7.91 and 7.43 for the control and bacteriocin GP1 respectively at the end of storage period (28 days) when stored at 4°C. However, the pH showed a decreasing trend with the increase in period of storage for the samples stored at 0°C. The TVB-N content of the bacteriocin treated samples stored at 4°C remained within the limit of acceptability (35 mg/100 g) at the 21st day. The TMA level also remained within the acceptable limit of 10–15 mg/100 g at the 21st day in the case of bacteriocin-treated samples. The application of bacteriocin GP1 in the stored fish was effective in controlling the growth of coliforms, Aeromonas sp., Lactobacillus sp. and Vibrio sp. in the treated fish samples. The study concluded the prospects of bacteriocin GP1 as a biopreservative in storage of fish and fish products.